3D graphics as an effective tool for online advertising - Chebotarova, I.; Yukhnova, К.; Polozov, О.; Mendielieva, M. (Oktan print, 2025)
There is an enormous variety of goods and services offered in the modern online marketplace. Very often, a single product category is produced by hundreds of different companies, leaving consumers overwhelmed by this variety. Consequently, one of the most effective approaches in online advertising is the development of creative solutions capable of distinguishing a specific product on the market and producing memorable advertising content. The use of 3D (three-dimensional) models to create engaging characters as well as product and object visualizations can significantly enhance advertising effectiveness. This has determined the relevance of studying the specific features of using 3D graphics in online advertising.
Keywords: 3D animation; 3D graphics